THE EFFECTIVENESS OF ACARICIDAL PREPARATIONS AT RABBIT PSOROPTIC MANGE AND THEIR INFLUENCE ON HEMATOLOGICAL INDICES - Kruchynenko, O. V.; Lisnyi M. О. (Scientific Progress & Innovations, 2019)
Rabbit psoroptic mange (common scab) is a widely spread acariform rabbit disease in Ukraine. The ani-mals are diseased with it from the second month of life. The disease is caused by Acariformes of Psoroptes cuniculi species (Delafond, 1859), and it is manifested by the lesion of mainly internal surface of one or two concha, forming massive, solid scabs and plugs in them, which is accompanied by otitis of various character, scratching the diseased ears with limbs, spreading inflammatory process on the concha base skin, neck and limbs and its transition to the tympanum and internal ear with further meningitis complication. The research results concerning therapeutic effectiveness of vegetable oil with 10% of garlic, ozonized olive oil and 2 % brovermectin (1 ml of the preparation contains 20 mg of ivermectin) and their effect on hematological indi-ces of rabbits are presented in the article. To conduct the experiment on the private farm in the village of Bobrivnyk, Zinkiv district, Poltava region, three groups of Flandre breed rabbits were formed (n=6), 9−12 months of age, which were spontaneously infected with P. cuniculi ear tick. Blood for hematological study was selected before treatment and on the 14th day. Vegetable oil with garlic and ozonized olive oil were used locally three times a day, and 2 % brovermectin was administered orally for 5 days. The effectiveness of cu-rative treatments was estimated according to extense- and intense effectiveness (EE and IE) indices on the 14th day from the beginning of treatment. Using oil and official preparation did not have any side effects, which was confirmed by clinical observations. In case of rabbits’ infestation with P. cuniculi ticks, the thera-peutic effectiveness of vegetable oil with 10% garlic, ozonized olive oil and 2 % brovermectin made 100% on the 14th day. Rabbit psoroptic invasion is manifested by changing the indices of blood stream, and namely: erythrocytopenia, leukocytopenia, lymphocytopenia, decreasing hemoglobin content, and monocyto-sis. After rabbits’ treatment, on the 14th day, the blood stream indices were gradually normalized, which was manifested by reliable increasing hemoglobin content, the number of erythrocytes, leukocytes, and lympho-cytes (p<0.05) and decreasing the number of monocytes (p<0.05).